Kick frequency affects the energy cost of aquatic locomotion in elite monofin swimmers - Boitel, G.; Vercruyssen, F.; Alberty, M.; Nesi, X.; Bourdon, L.; Brisswalter, J. (European Journal of Applied Physiology, 2010)
The aim of this study was to evaluate the influence of kick frequency (K F) on the energy cost of aquatic locomotion in elite monofin (Mf) swimmers at the surface. Eight subjects of international calibre (4 females, 4 males) were requested to perform in a 50-m outdoor swimming pool: (1) a continuous multi-stage incremental test to determine maximal physiological responses and (2) a submaximal exercise composed of five constant Mf-swimming tests (600-m exercise, 5-min rest) at an intensity corresponding to 90% of the velocity at the maximal oxygen uptake ( [(V)O2max VO2max). The first submaximal Mf-swimming test was systematically conducted at a freely chosen K F (FCKF) and the other tests were performed at FCKF - 15%, FCKF - 10%, FCKF + 10% and FCKF + 20% in a random order. No significant effect of K F on ventilation, heart rate and blood lactate concentration was observed throughout the submaximal Mf-swimming tests. However, mean values in Ec or fraction of [(V)O2max VO2maxwere significantly lower during the FCKF + 10% condition as compared to those observed during the FCKF - 15% (-11.5 and -9.6%, respectively, P < 0.05) and FCKF - 10% (-10.4 and -9.3%, respectively, P < 0.05) conditions. In conclusion, the lack of significant differences between FCKF + 10% and FCKF or FCKF + 20% does not allow to identify a specific trend, but suggests the occurrence of an energetically optimal K F close to that freely chosen by the Mf swimmers. Variations in muscle activity level and active drag have been hypothesized to explain the observed differences in Ec consecutive to the selection of various K F.